Construction of an Integrated mCherry Red Fluorescent Protein Expression System for Labeling and Tracing in Lactiplantibacillus plantarum WCFS1 - Yang, Yao; Zhang, Wenjun; Huan, Hailin; Xia, Wenxu; Chen, Ying; Wang, Peijuan; Liu, Yanrong (Frontiers in Microbiology, 2021)
Various Lactobacillus strains have been studied to evaluate their protein expression and the functions of different proteins. However, a suitable tracer detection system is needed to examine the probiotic properties of Lactobacillus to the host. In our previous study, the red fluorescent protein mCherry showed the potential for application in the labeling of Lactiplantibacillus plantarum WCFS1. To develop an efficient tracer detection system, in this study, the mcherry gene was integrated into the chromosomes of L. plantarum WCFS1 by homologous recombination. Adjusting the spacer region to 9 bases increased the expression of mcherry regulated by the promoter ldhL, thereby enhancing fluorescence intensity. Compared with the plasmid expressing the fluorescent protein system in L. plantarum WCFS1, the integrated mCherry expression system showed better stability even under growth pressure without antibiotics. In addition to tracing, the integrated mCherry expression system was used to accurately quantify the number of colonies based on mcherry by qPCR. Moreover, the integrated mCherry expression system can be used to study cell adhesion of Lactobacillus and shows excellent performance without interfering with the plasmid expression system in L. plantarum WCFS1, which is suitable for studies of physiological function. The results of this study suggest that the integrated mCherry expression system in L. plantarum WCFS1 can be used to examine the distribution, colonization, and survival of lactic acid bacteria in vivo in order to determine the mechanism of its probiotic function, as well as lay the foundation for the expression, cell localization, and function identification of other functional proteins in lactic acid bacteria.